Strategi dan Tantangan Peternak Kambing dalam Menyambut Permintaan Aqiqah dan Idul Adha: Studi Kasus pada Usaha Adinda Aqiqah milik Pak Anto - Arofiani Mutmainah; Dina Cheetah Khairiyah; Habibah Ramadhani Nasution; Rafly Aditya Sambo; Septian Dwi Cahya; Zainarti Zainarti (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2025)
The demand for goats for religious rituals such as aqiqah and qurban during Eid al-Adha has shown a significant upward trend each year, in line with the growing awareness among Muslims to observe religious practices in accordance with Islamic law. This study aims to explore the strategies employed and the challenges faced by traditional goat farmers in responding to this evolving demand. A descriptive qualitative approach was used, with data collected through in-depth interviews, field observations, and documentation. The subject of this study was Mr. Anto, an experienced goat farmer and trader who manages the “Adinda Aqiqah” business in Medan City. The findings reveal that Mr. Anto’s main strategies include stock management through the raising of hundreds of goats of various breeds (Kacang, Etawa, and sheep), the selection of high-productivity superior breeds, and the setting of competitive selling prices for both qurban and aqiqah needs. On the other hand, the primary challenges encountered include limited infrastructure, particularly at sales locations, animal health risks due to adverse weather conditions, and the lack of effectiveness in using social media as a marketing tool to reach a wider consumer base. These findings offer a clear picture of how traditional livestock practices adapt to market demands, while also highlighting the need for improvements in technology, marketing, and policy support to enhance competitiveness in this dynamic, seasonal market.